2014
DOI: 10.1002/celc.201402191
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer versus Hydrogen Bonding: The Reduction of Ubiquinone Q2 Incorporated in a Self‐Assembled Monolayer in Unbuffered Aqueous Solution

Abstract: The electrochemical reduction of ubiquinone Q2 (UQ2) in unbuffered aqueous media was investigated over a pH range of 2 to 11, and the results were compared to those obtained in our previous work in buffered solutions. The short isoprene chains of UQ2 were incorporated in a self‐assembled monolayer. Analysis of the mechanism and a study in D2O solutions allowed us to demonstrate the important role of hydrogen bonding in the stabilization of the reduced species, also in water. If the concentration of H+ is low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Quinones and hydroquinones play a key role in many biological systems, e.g. in photosystems I and II, because of their capability to transfer electrons and protons 4,5 . The quantum yield of fluorescence ( F  can also be highly increased in CTCs, as exemplified by the distyrylbenzene -dicyanodistyrylbenzene CTC, with  F up to 60% against a few % for both partners 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Quinones and hydroquinones play a key role in many biological systems, e.g. in photosystems I and II, because of their capability to transfer electrons and protons 4,5 . The quantum yield of fluorescence ( F  can also be highly increased in CTCs, as exemplified by the distyrylbenzene -dicyanodistyrylbenzene CTC, with  F up to 60% against a few % for both partners 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Several electrochemical studies have been carried out regarding the reduction of quinones, mainly to gain insights about the underlying mechanisms and the effects provoked by changing conditions such as electrolytic medium and electrode surface, among others [ 22 ]. A study on the effects of hydrogen bonds in different Q/HQ systems in non-aqueous media showed that the presence of oxygenated functional groups on the surface of the electrode could affect the interaction between dissolved compounds and the surface, which had a significant impact on the electron transfer process [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the quinones are incorporated into a self‐assembled monolayer, the global two electrons – two protons electrochemical reduction, in aqueous media, can be described on the basis of a nine‐member square Scheme . However, the reaction proceeds through proton‐coupled electron transfer in aqueous media, but not in unbuffered media . In the solid‐state, in addition to the reduced and oxidized forms, another structure, called quinhydrone, can be stabilized, which combines both redox species.…”
Section: Introductionmentioning
confidence: 99%